What papers should I cite from my reading list? User evaluation of a manuscript preparatory assistive task - Foo, Schubert (2016)
Literature Review (LR) and Manuscript Preparatory (MP) tasks are two key activities for researchers. While process-based and technologicaloriented interventions have been introduced to bridge the apparent gap between novices and experts for LR tasks, there are very few approaches for MP tasks. In this paper, we introduce a novel task of shortlisting important papers from the reading list of researchers, meant for citation in a manuscript. The technique helps in identifying the important and unique papers in the reading list. Based on a user evaluation study conducted with 116 participants, the effectiveness and usefulness of the task is shown using multiple evaluation metrics. Results show that research students prefer this task more than research and academic staff. Qualitative feedback of the participants including the preferred aspects along with critical comments is presented in this paper.